Claude Monet - Connolly, Sean, 1956- (Lives of the artists, 2005)
Examines the life and long career of nineteenth-century French artist Claude Monet, a painter associated with the impressionist movement, looking at his evolving style, discussing historic events that were taking place during his lifetime, and considering Monet's legacy to other artists.